Case Study : Sri Kejai Enterprise / Adlina Anati Abdul Aziz - Abdul Aziz, Adlina Anati (2020)
This case study is based on Sri Kejai Enterprise which is located in Kuala Ketil, Kedah. The main product produce by the company is rempeyek. An interview session was done through online platform and by using google form to extract the information needed for this case study. In this case study, SWOT analysis is used to analyse the strengths, weaknesses, opportunities and threats of the company. Also, Consumer Trend Canvas (CTC) template is used to collect and analyse information about consumer trends and uncovering innovation opportunities. From the information extracted, a few problems faced by Sri Kejai Enterprise can be identified. The major problem faced by this company is they do not have machine to produce large quantity of product due to high demand from customers for certain period of time. The company also faced problem regarding the packaging of product and marketing strategy. Therefore, a few alternative solutions are suggested to solve the problems such as purchasing a high quality machines, improve packaging types and use paid advertising on social media to improve the marketing strategy.